HYDROPROCESSING OF PETROLEUM FRACTIONS OVER MODIFIED ALUMINIUM OXIDE CATALYSTS - Tuktin B.T.; Shapovalova L.B.; Yeleussin K.O.; Abilmagzhanov A.Z.; Kubasheva A.Zh. (Academic Scientific Journal of Chemistry, 2020)
The hydro processing of gasoline and diesel oil fractions over aluminum-nickel-molybdenum catalysts modified by additives HY, ZSM-5, phosphorus and rare earth elements were studied. At the hydro processing of straight-run gasoline over NiO-MoO3- Ce2О3-Р2О5–ZSM(30%)-Al2O3 the content of isoalkanes increases in comparison with the initial from 26.3 to 35.7- 38.3% at 320-400о С. The octane number of refined gasoline at 400о С is 83.7 (RON) and 69.7 (MON). The sulfur content decreases from 0.037% (initial gasoline) to 0.0022%. At hydro processing of straight-run gasoline over NiO-MoO3-La2О3-Р2О5-ZSM-Al2O3 in the range of 320– 400 o C the content of isoalkanes is 30.7- 44.3%. The octane number of refined gasoline at 400o C is maximum and is equal to 91.8 (RON) and 72.4 (MON). Under these conditions the sulfur content decreases from 0.0092% to 0.0028%. The optimal conditions for the hydro processing of straight-run gasoline were revealed: T=400˚С, V=2 h-1, Р = 4.0MPa. The catalyst NiO-MoO3-La2О3-Р2О5-ZSM-HY-Al2O3 has the highest hydro desulfurizing activity, the residual sulfur content at 400o С is 0.0012%. The catalyst NiO-MoO3-La2О3-Р2О5-ZSM-Al2O3 has the highest hydro desulfurizing activity. At hydro processing of straight-run diesel fraction on this catalyst under optimal conditions the sulfur content decreases from 0.6400 % to 0.0740 % and during hydro processing of a straight-run diesel fraction with a higher sulfur content 0.8042% - up to 0.053%, which, apparently, is associated with the presence in the feedstock of various types of organosulfur compounds. The lowest pour point and cloud point under optimal conditions reaches minus 39.6o С and minus 30.5o С respectively. Thus, developed modified zeolite-containing catalysts for the hydro processing of gasoline and diesel fractions carry out hydro processing, hydro isomerization and hydrogenation in one stage. The developed catalysts make possible to obtain high-octane low-sulfur gasoline and low-solidification low-sulfur diesel fuel.